Senior manager leadership competencies for quality residential aged care: an Australian industry perspective - Nathan Dawes; S. M. Topp (BMC, 2022)
Abstract Background Documented poor quality and standards of care in Australia's residential aged care (RAC) sector have highlighted a need to better understand the role of and skills required by, RAC senior management personnel to address these concerns. This study examined which senior management leadership skills and personal qualities are necessary to deliver and strengthen the quality of RAC, with the aim of improving understanding of the professional development needs of leaders in the sector. Methods We conducted 12 in-depth interviews with Australian aged care industry experts, including academics, and representatives from the primary health network, consumer, and provider advocate groups. Abductive, thematic analysis incorporated coding derived from existing leadership skills frameworks as well as inductively identified themes. Results Identified leadership skills were grouped into five domains including i) workforce development and retention, ii) governance and business acumen; iii) health systems knowledge; iv) stewardship and v) responding to regulatory and political contexts. Skills particularly emphasised by participants were those required to recruit and retain a skilled workforce, manage relationships, and promote a positive organisational culture and employee wellbeing. Conclusions RAC senior managers require a complex mix of business, human resource management, and clinical skills to deliver quality care in Australia's complex RAC setting. The lack of any professional development framework to guide the acquisition or updating of those skills is a concern.